Governing bodies, creating gay spaces. Policing and security issues in 'gay' downtown Toronto - Valverde, Mariana (The British journal of criminology, 2003)
In contrast to criminological studies of gay-specific hate crimes, this study focuses not on crimes but on the governance of security in a major global centre of lesbian/gay community life, namely Toronto's gay village, with security defined as the attempt to guarantee order mainly by governing space and time. Based on interviews with community activists, business owners and police officers, as well as examinations of criminal justice data, gay and mainstream newspapers, and the files of the Alcohol and Gaming Commission of Ontario, the authors document the complex layers of private (both formal and informal) policing that uneasily coexist with the actions of the public police and of regulatory officials such as municipal licensing officers. The research site consists of two kinds of spaces: the commercial spaces of bars and baths, which have their own unique systems for ensuring security for the patrons and for the premises, and the streets, particularly the legal space that is created through municipal and provincial permits during Pride Day celebrations. In general, the authors document a growing trend toward self-policing in both businesses and community events, and a commercialization of security services that extends to the public police, insofar as many public police work as paid duty officers' and act like security guards for the organization holding events. The implications of this study for theoretical work on governance relations, particularly on the governance of security, are developed throughout